Preliminary Analysis of Atmospheric Front-Related VHF Propagation Enhancements for Navigation Aids - Tomasz Aleksander Miś; Wojciech Kazubski; Mikołaj Zieliński (Sensors)
The tropospheric storm fronts were found to cause disruptions in the propagations of VHF (Very High Frequency) radio signals, elevating their signal levels. This is especially important for VHF radio navigation systems, such as VOR (VHF Omnidirectional Range), used for naval, airborne and terrestrial transportation, and as the assisting navigation aids for the smaller vehicles forming the Internet of Drones. This article describes this disruptive phenomenon analytically and shows an experimental verification of the developed formula, presenting the increase in relative VHF signal range by ~1.8 times with decreasing tropospheric refraction. Contrary to popular VHF propagation models, largely averaged and statistics-based, the shown formula can be used simultaneously with meteorological predictions, contributing significantly to the mitigation of radio navigation issues related to stormy weather in the operative range of the Internet of Drones.